ĐIỀU TRA SƠ BỘ BỆNH TIM MẠCH CỦA CÁN BỘ VÀ CÔNG NHÂN CÔNG TY B LÀM NHIỆM VỤ TẠI KHU VỰC BỊ RẢI CHẤT ĐỘC DA CAM / DIOXIN TRONG CHIÊN TRANH - Ngô, Thanh Nam; Hoàng, Đức Hậu; Vũ, Hoài Tuân; Trần, Ngọc Tâm (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
PRELIMINARY INVESTIGATION OF CIRCULATORY DISEASES OF SOLDIERS AND WORKERS WORKING IN THE AGENT ORANGE SPRAYED REGIONS IN THE WAR In this report we present the results of a preliminary investigation of medical personal history of prevalent hypertension, heart arrhythmias and cardiac ischaemia and the exposure to Agent Orange/Dioxin residues in the environment of the soldiers and workers of the company B working in the orange agent sprayed regions during the war in the province Kon Tum. The finding is expected to give some directions for further research.